Sources of stress and coping mechanisms among Filipinas in West Germany and Holland. [article]. - Samonte, Elena L.
The study describes the values problems and coping mechanisms of Filipinas in West Germany and Holland. It discusses these coping mechanisms in the light of the Filipina's sociocultural background and delineates the possible areas of intervention. Data were obtained from both primary (participant observation, interviews, focused group discussions) and secondary sources(newspaper articles). The subjects were Filipinas who went to Europe to work, to marry, to tour, or to join their husband.